SYSTEMS FOR FORMATION OF ENVIRONMENTAL SAFETY CULTURE IN STUDENTS AT TECHNICAL HIGHER EDUCATIONAL INSTITUTIONS - Hamidovna, Ayubova Indirakhon (International Journal of Psychosocial Rehabilitation, 2020)
This article was written with the aim of improving the systems of formation of environmental safety culture among students of technical higher educational institutions. The following research objectives are identified in the article and their solutions are given: a theoretical analysis of the definition of the process of formation of an environmental safety culture among students of technical higher educational institutions; identification of didactic, acmeological and axiological capabilities of the system of forming a culture of environmental safety among students; improving the model of infrastructure of systems for the formation of an environmental safety culture among students; determination of methods, forms, means of innovative educational strategy of the process of forming a culture of environmental safety among students and the development of recommendations and proposals to improve its effectiveness".